Experimental investigation of the effect of different process variables on the viscosity of sulfonated polyacrylamide copolymers - Isa , M. Tan (2017)
Increasing the viscosity of injected water by the addition of polymer improves the displacement efficiency during the water flooding process. In this study, a sulfonated polyacrylamide copolymer has been added to salt water.